2021
DOI: 10.1080/20008198.2021.1975952
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in a wide range of trauma symptoms after victimization and accidental traumas: a cross-sectional study in a clinical setting

Abstract: Background There are large gender differences in PTSD prevalence. Gender differences in a wide range of trauma symptoms including disturbances in self-organization have not been extensively researched. Objective To explore gender differences in a wide range of trauma symptoms by comparing victimization trauma (VT) with accidental trauma (AT). Method A cross-sectional study of 110 traumatized patients attending a mental health outpatient clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…This paper scored 80% in quality assessment. Søegaard et al ( 2021 ) reported a similar finding: sexual assault was experienced by significantly more women; experiences of combat were significantly higher among men. This paper scored 60% in quality assessment.…”
Section: Resultsmentioning
confidence: 74%
See 4 more Smart Citations
“…This paper scored 80% in quality assessment. Søegaard et al ( 2021 ) reported a similar finding: sexual assault was experienced by significantly more women; experiences of combat were significantly higher among men. This paper scored 60% in quality assessment.…”
Section: Resultsmentioning
confidence: 74%
“…Giarratano et al ( 2020 ) reported higher overall CPTSD symptoms among women but did not specify which symptoms. In Søegaard et al ( 2021 ), where there were no overall differences in DESNOS scores, men had significantly higher cluster scores for negative self-perception (e.g. shame and guilt) and alterations in systems of meaning (e.g.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations